مشكلات ترقية كفاءة الطلبة في اللغة العربية - Fadhilah Samhabib (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
Competence is skills that are closely related to the effectiveness of person’s performance in a particular field. Similarly in education, competence is the key to student success, and also the great competence of the majors chosen by the students will lead to increased quality of majors. Arabic Language Education Department in IAIN Kendari is a department that prepares students to become educators and scientists in Arabic language which has competence in Arabic were nice and had a high competitiveness. This research uses descriptive analysis method with qualitative approach based on case study design. The data collection is done by in-depth interviews, observation, documentation, and open questionnaire. The results showed (1) a strategy to increase student competence in Arabic language on Arabic language education department at IAIN Kendari still ineffective that was described by least of activities that support the increased student’s competence in Arabic language and also its lack of consistency in implementing additional programs for students of Arabic language education department (2) the helping and resistoring factors to increase student’s competence contained on lecturer’s performance in the classroom, facilities of language learning, and student’s motivation. lecturer’s performance in the classroom has given many help to increase student’s competence in Arabic, facilities to assist in learning the Arabic language still needs to be cared and activated again or making the new and interesting activities, and student’s motivation in the study of Arabic is still lacking is due to the absence of another place for practicing the Arabic language competencies that they have acquired, and also the lack of student’s interest in attention of learning at the classroom caused by the bored atmosphere of the class (3) the problem solving by formulating a strategy based on suggestions and feedback from lecturers and students in Arabic language education department is a path that can be taken by Arabic language education department in IAIN Kendari to improve student’s competence in Arabic language.